Playground, Horniman Circle Garden - Ghosh, Ayan (2023)
The Horniman Circle gardens are laid out with walkways and used as a playground by kids. People also access the garden for exercising early in the morning. The Circle Garden has been repurposed by the Kala Ghoda Association and every year, since 1999, the garden has been used as a venue for events during the Kala Ghoda Arts Festival.